The Obesity–Impulsivity Axis: Potential Metabolic Interventions in Chronic Psychiatric Patients - Sfera, Adonis; Osorio, Carolina; Inderias, Luzmin Acosta; Parker, Victoria; Price, Amy I.; Cummings, Michael (Frontiers in Psychiatry, 2017)
Pathological impulsivity is encountered in a broad range of psychiatric conditions and is thought to be a risk factor for aggression directed against oneself or others (1). Recently a strong association was found between impulsivity and obesity which may explain the high prevalence of metabolic disorders in individuals with mental illness even in the absence of exposure to psychotropic drugs (2-5). As the overlapping neurobiology of impulsivity and obesity is being unraveled, the question asked louder and louder is whether they should be treated concomitantly (6-7). The treatment of obesity and metabolic dysregulations in chronic psychiatric patients is currently underutilized and often initiated late, making correction more difficult to achieve. Addressing obesity and metabolic dysfunction in a preventive manner may not only lower morbidity and mortality, but also the excessive impulsivity, decreasing the risk for aggression. In this review we are looking at potential early interventions for metabolic dysregulation in psychiatric patients, including medical, dietary and physical therapy approaches.